Type VI Choledochal Cyst; A Case Report and Review of the Literature - Serdar Aslan; Ömer Görgel; İsmet Miraç Çakır (The Egyptian Journal of Radiology and Nuclear Medicine, 2020)
Abstract Background Choledochal or common bile duct (CBD) cysts are congenital cystic dilatation of any part of the bile ducts. It has been classified into five main types by Todani et al. Isolated cystic duct cysts are not included in this classification. It is extremely rare, and there are a limited number of cases in the literature. Case presentation A 34-year-old male patient was admitted to our hospital with right upper quadrant (RUQ) pain experienced intermittently for the past year. His medical history and laboratory findings were normal. Physical examination revealed tenderness in the RUQ. Abdominal ultrasonography shows that a thin, tubular, cystic lesion was associated with the CBD. On magnetic resonance imaging (MRI) and magnetic resonance cholangiopancreatography (MRCP), a saccular dilatation was observed in the middle part of the cystic duct. Isolated cystic duct dilatation was considered with current imaging findings. Laparoscopic cholecystectomy and cyst excision were performed. Surgery findings and histopathological examination of the excised cyst confirmed the diagnosis. Conclusion Isolated dilatations of the cystic duct are extremely rare, and familiarity with this anatomic variation and its early diagnosis can prevent complications such as inflammation and malignancy and guide the surgery. The most effective noninvasive imaging method in diagnosis is MRCP. Also, we recommend that it be classified as a new type with the name type VI biliary cyst, in addition to Todani classification.